1988
DOI: 10.1080/00050068808255619
|View full text |Cite
|
Sign up to set email alerts
|

Australian normative study of the achenbach child behaviour checklist

Abstract: This study is an Australian replication of the Achenbach and Edelbrock normative study on the Child Behaviour Checklist (1981). Thesample of 1,300children was obtained from Sydney and surrounding suburbs and therefore is urban and metropolitan. Norms for the Child Behaviour Problem scores are considerably higher than for American children. and in general. norms for the total Social Competence scores are lower. "Cut-ofT'percentile equivalents to the American clinical cut-orfs are provided, though it will be nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 11 publications
1
28
2
Order By: Relevance
“…Items for the aggressive narrow band include 'physically attacks people' and 'gets in many fights'. Hensley (1988) reported a normative study of the CBCL/4-18, which supported the reliability and content and construct validity of the measure in the Australian population. Bond, Nolan, Adler, and Robertson (1994) compared Melbourne school-aged children with data from the USA and Sydney and concluded that US normative problem data from the CBCL/4-18 were appropriate for use with Australian children.…”
Section: Aggressive Behaviourmentioning
confidence: 70%
“…Items for the aggressive narrow band include 'physically attacks people' and 'gets in many fights'. Hensley (1988) reported a normative study of the CBCL/4-18, which supported the reliability and content and construct validity of the measure in the Australian population. Bond, Nolan, Adler, and Robertson (1994) compared Melbourne school-aged children with data from the USA and Sydney and concluded that US normative problem data from the CBCL/4-18 were appropriate for use with Australian children.…”
Section: Aggressive Behaviourmentioning
confidence: 70%
“…Further assessment is warranted when T scores above 60 are obtained. Australian data have shown the structure of the CBCL to be appropriate for Australian children (Heubeck, 2000), with some studies showing a higher level of problem behaviour in Australian children than American children (Hensley, 1988;Sawyer et al, 2001), and others showing no difference (Bond, Nolan, Adler, & Robertson, 1994).…”
Section: Methodsmentioning
confidence: 97%
“…The social competence scales examine the child’s adaptive functioning including their activities, and social and school performance [42]. Behavioral and emotional functioning is assessed by 118 items, which describe an array of problems that children might experience [42,43]. Validity and reliability data were obtained in a sample of over 5,000 children and were found to be moderate-to-high and high, respectively [44].…”
Section: Methodsmentioning
confidence: 99%